Digital Leadership Transformation In Enhancing Generation Z Employee Performance - Adriani Gunawan; Didi Mulyadi; Fikry Ramadhan Suhendar (Doctoral Program of Social Science Pasundan University, 2025)
The rapid evolution of the digital landscape has forced organizations to redefine their leadership paradigms to maintain workforce productivity, particularly among the tech-savvy Generation Z. This study aims to explore the role of Digital Leadership Transformation in enhancing the performance of Generation Z employees. Using a qualitative descriptive approach, data were gathered through semi-structured interviews with leaders and Generation Z subordinates in various digital-based industries, complemented by thematic analysis. The findings indicate that digital leadership is not merely about technological proficiency but involves a fundamental shift in mindset toward transparency, agility, and collaborative empowerment. Generation Z employees perceive digital leadership transformation as a critical driver for their performance, as it fosters a work environment that values flexibility and rapid feedback. The study identifies three key pillars of effective digital leadership: digital vision, digital social capital, and digital adaptability. These elements collectively minimize the